Estimation of failure parameters for finite element simulations based on a single state of stress and arbitrary stress-strain relation: - Voormeeren, L.O.; Tang, L.; Walters, C.L.; Vredeveldt, A.W. (2014)
Crash analysis in the maritime and offshore industry typically relies on failure criteria that are based only on uniaxial states of stress. However, it is well known that the failure strain depends on the state of stress, and the state of stress in ship collisions is not necessarily uniaxial. Although more detailed failure models are routine in other industries, the cost of finding the parameters for these models remains a barrier within the maritime and offshore industry. This paper explores an approach of applying the Modified Mohr-Coulomb (MMC) failure criterion based on a single tension test. This is based on the observation that there is only a single independent calibration parameters when a von Mises yield locus and plane stress are assumed. The MMC yield condition is also generalized by applying it to an arbitrary stress versus strain relationship, which does not follow the power hardening law. Results of impact tests on small-scale cryogenic storage tanks filled with water and air are presented and are used to validate the adjustments made above. This validation test also shows how the above findings can be applied to storage tanks for LNG fuel on inland waterway ships.